Case-control study of acute renal failure in patients with cystic fibrosis in the UK. Issue 6 (1st February 2008) - Smyth, A; Lewis, S; Bertenshaw, C; Choonara, I; McGaw, J; Watson, A
Abstract : Background: There has been a recent increase in the number of reported cases of acute renal failure (ARF) in cystic fibrosis (CF). A case-control study was conducted to determine the factors which are associated with an increased risk of ARF. Methods: 24 cases of confirmed ARF were identified in patients with CF from 20 UK CF centres presenting between 1997 and 2004. Using the UK CF database, sex- and age-matched controls were identified. Risk factors were analysed by conditional logistic regression and Mantel-Haenszel analysis. Results: 21 of the 24 patients with ARF had received an aminoglycoside at the time of their episode of ARF or in the preceding week compared with only 3 of 42 controls during the same time period (OR 81.8, 95% CI 4.7 to 1427, p<0.001). In the year before the episode of ARF, significantly more cases than controls had received gentamicin (19/24 cases vs 1/42 controls, p<0.001). The numbers receiving tobramycin were similar (9/24 cases vs 16/42 controls, p = 0.9). A known risk factor for renal impairment (prior renal disease, acute dehydration or long-term treatment with a nephrotoxic drug) was present in 18/24 cases and 7/42 controls (OR 24.0, 95% CI 3.1 to 186.6, p = 0.002). Conclusions: In patients with CF the use of an intravenous aminoglycoside is a risk factor for ARF; gentamicin is more nephrotoxic than tobramycin. Most patients who develop ARF have a risk factor which necessitates withholding aminoglycosides or more closely monitoring their use.